2021
DOI: 10.1108/cg-11-2020-0527
|View full text |Cite
|
Sign up to set email alerts
|

Corporate governance mechanisms and firm performance: empirical evidence from medium and large-scale manufacturing firms in Ethiopia

Abstract: Purpose This study aims to examine the impact of corporate governance mechanisms on financial and non-financial aspects of firm performance in medium and large-scale manufacturing firms in Ethiopia. Design/methodology/approach The cross-sectional survey and simple random sampling methods are adopted while the data collection is through a questionnaire that covers five corporate governance indicators consisting of the board independence, board effectiveness, shareholders role, internal audit effectiveness (IA… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 16 publications
(17 citation statements)
references
References 126 publications
1
11
0
Order By: Relevance
“…We obtained data on a list of medium- and large-scale manufacturing firms from the Ministry of Industry and the Central Statistical Agency. The data showed that up to the end of the year 2018, 3,520 medium- and large-scale manufacturing firms were registered and operating in Ethiopia (Erena et al , 2022). A total of 200 firms were chosen at random for this study to collect the relevant data.…”
Section: Methodsmentioning
confidence: 99%
“…We obtained data on a list of medium- and large-scale manufacturing firms from the Ministry of Industry and the Central Statistical Agency. The data showed that up to the end of the year 2018, 3,520 medium- and large-scale manufacturing firms were registered and operating in Ethiopia (Erena et al , 2022). A total of 200 firms were chosen at random for this study to collect the relevant data.…”
Section: Methodsmentioning
confidence: 99%
“…Compared with positive reports, negative media reports can play a more important role in public opinion and supervision ( Jin and Qin, 2021 ). Erena et al (2022) and other studies found that the media reports and exposure of negative enterprise news will lead to a substantial decline in enterprise stock prices, affecting enterprise reputation and rating, and leading to a decline in enterprise investment capabilities ( Li et al, 2018 ). Wang et al (2022) deeply studied the relationship between enterprise performance and market response, and found that negative media reports can trigger a larger market response, thus playing the role of enterprise governance ( Han et al, 2021 ).…”
Section: Research Hypothesismentioning
confidence: 99%
“…However, in the context of Africa, there is still a paucity of research about the role of corporate governance in SDGs. Most studies examining the impact of corporate governance in African firms’ decision-making processes have focused on firm performance (Mangena et al , 2012; Darko et al , 2016; Assenga et al , 2018; Erena et al , 2022; Abang’a et al , 2022) and corporate reporting (Waweru et al , 2019; Chijoke-Mgbame et al , 2020). Thus, our knowledge about whether and how corporate governance contributes to the SDGs or sustainable development principles in Africa remains very limited.…”
Section: Corporate Governance and Sustainable Development In Africamentioning
confidence: 99%